The Teaching-learning Conditions for Quality Education in inclusive Schools - Choudhuri, Rashmi (JOURNAL OF INDIAN EDUCATION, 2010)
There has been recent theoretical and policy interest in the two areas of quality education and inclusive education. Inclusive education has been already launched in our country through Sarva Siksha Abhiyan. This paper discusses the concepts of quality education and inclusion and then reflects at the Indian scenario with a focus on teaching-learning conditions in schools where inclusion is promoted.